2019
DOI: 10.1038/s41467-019-11852-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining charitable giving in real-world online donations

Abstract: The current study uses big data to study prosocial behavior by analyzing donations made on the GoFundMe platform. In a dataset of more than $44 million in online donations, we find that 21% were made while opting to be anonymous to the public, with survey results indicating that 11% of these anonymous donations (2.3% of all donations) are not attributable to any egoistic goal. Additionally, we find that donors gave significantly more to recipients who had the same last name as them. We find evidence that men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…In addition to the fixed effects of interest, we modelled other variables with a presumed association with altruistic motivation, namely age, gender, socio-economic status and employment. Briefly, 1) age has been shown before to be positively associated with prosocial tendencies (Matsumoto et al, 2016;Sze et al, 2012); 2) gender may modulate prosocial behaviour (Sisco & Weber, 2019;Willer et al, 2015), particularly in stressful situations (Shelley, 2000); and 3) socio-economic and employment status could compromise one's ability to carry out some types of altruistic acts (e.g., money donations), and affect subjective wellbeing, which has been previously linked with altruism (Brethel-Haurwitz & Marsh, 2014).…”
Section: Modelling the Relation Between Everyday Altruism Covid-19 Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the fixed effects of interest, we modelled other variables with a presumed association with altruistic motivation, namely age, gender, socio-economic status and employment. Briefly, 1) age has been shown before to be positively associated with prosocial tendencies (Matsumoto et al, 2016;Sze et al, 2012); 2) gender may modulate prosocial behaviour (Sisco & Weber, 2019;Willer et al, 2015), particularly in stressful situations (Shelley, 2000); and 3) socio-economic and employment status could compromise one's ability to carry out some types of altruistic acts (e.g., money donations), and affect subjective wellbeing, which has been previously linked with altruism (Brethel-Haurwitz & Marsh, 2014).…”
Section: Modelling the Relation Between Everyday Altruism Covid-19 Tmentioning
confidence: 99%
“…These characteristics seem applicable to the pandemic, wherein the fear of infection has co-occurred with that of losing one's job and/or access to essential goods like medication, food, or even toilet paper. However, the notion of a fundamentally selfish human nature is called into question by the ubiquitous nature of everyday altruism in modern societies (Mattis et al, 2009;Sisco & Weber, 2019), and by instances of extraordinary altruism in highly risky (e.g., heroic rescues; https://www.carnegiehero.org/) or costly scenarios (e.g., non-directed organ donation; Brethel-Haurwitz & Marsh, 2014). Importantly, it has been suggested that challenging contexts may in fact promote rather than hinder altruistic motivation (Buchanan & Preston, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, they might arbitrarily control the dissemination of information signaled by their behavior -I would call it selective signaling. This notion challenges the predominant view that anonymous giving is a pure reflection of selfless intents (psychological altruism; Batson, 1991;Sisco & Weber, 2019). Thus, I believe that future research should further delve into the deliberate anonymization of prosocial behavior.…”
mentioning
confidence: 89%
“…Raihani (2014) found that roughly 5% of 3,945 donations anonymously donated on an online fundraising website. Moreover, Sisco and Weber (2019) collected records of actual contribution to more than 9000 projects from roughly 558,000 individuals on the GoFundMe. They discovered that 21% of the donation ($10,247,209) was made anonymously.…”
mentioning
confidence: 99%
“…The study found that contributors tended to conceal information when they are privacy sensitive, when the campaign they are contributing to has received greater public exposure that may put them under a greater scrutiny, or when they are exhibiting a behavior that can be negatively perceived by the public such as contributing too large or too small amount of money, or making a self-contribution towards their own campaigns [7]. Another research, this time in a donation-based crowdfunding context, examining 558,067 individual donation transactions on GoFundMe between January 2012 and June 2016 revealed that 21% of them were made anonymously [8]. This number is almost five times higher than anonymous donations made on another popular fundraising platform in the UK between 2007 and 2013, BMyCharity, which only constituted 4,6% [9].…”
Section: Literature Reviewmentioning
confidence: 99%